Impact of reduced Arctic sea ice on Greenland ice sheet variability in a warmer than present climate. Issue 11 (13th June 2014) - Koenig, S. J.; DeConto, R. M.; Pollard, D.
Abstract A global climate model with interactive vegetation and a coupled ice sheet‐shelf component is used to test the response of the Greenland ice sheet (GIS) to increased sea surface temperatures (SSTs) and reduced sea ice (SI) cover during the mid‐Pliocene warm period (∼3 Ma) as reconstructed from proxy records. Seasonally open water in the Arctic and North Atlantic are shown to alter regional radiation budgets, storm tracks, and moisture and heat advection into the Greenland interior, with increases in temperature rather than precipitation dominating the ice sheets response. When applied to an initially glaciated Greenland, the presumed warm, ice‐free Pliocene ocean conditions induce rapid melting of nearly the entire ice sheet and preclude a modern‐like GIS from (re)growing, regardless of orbital forcing. The sensitivity of Greenland to imposed Pliocene ocean conditions may have serious implications for the future response of the ice sheet to continued warming in the Arctic basin.